Pengaruh Audit Operasional dan Pengendalian Internal Terhadap Kinerja Karyawan - Manuaba, Ida Ayu Dewi Prayogi; Muliartha RM, Ketut (E-Jurnal Akuntansi; Vol 28 No 1 (2019), 2019)
The research objective is to determine the effect of operational audits and internal controls on employee performance. This research was conducted at the hospitality service company Ayodya Resort Bali. Data collection was conducted through interviews and questionnaires with a sample of 40 respondents who were auditees from the accounting department, human resource department, sales and marketing department, engineering department, front office department, food and beverage department, housekeeping department, and security department. The data analysis technique used is multiple linear regression analysis. Based on the result of the study indicate that operational audits and internal control have a positive effect on employee performance at the Ayodya Resort Bali hotel. Keywords : Operational audit, internal control, employee performance.